39. PATIENT DEMAND FOR PHARMACEUTICAL CARE SERVICES AT THE FAMILY MEDICINE CLINIC, PHAM NGOC THACH UNIVERSITY OF MEDICINE: A CROSS-SECTIONAL STUDY IN 2023 (Vietnam Journal of Community Medicine, 2025)
Introduction: Understanding patient demand for pharmaceutical care services is crucial for optimizing healthcare delivery, prompting a survey at the Family Medicine Clinic (FM).Aim: Survey the demand for pharmaceutical care services at the FM, Pham Ngoc Thach University of Medicine in 2023.Method: Descriptive cross-sectional study. A convenience sample method was conducted from August 2022 to May 2023, involving 424 patients who underwent medical examinations at the FM, Pham Ngoc Thach University of Medicine.Results: Most patients required the use of pharmaceutical care services at the Clinic again, accounting for 86.8%. The level of demand expression is high in 3 groups of needs, specifically, the need to check the suitability of prescriptions, the need for drug information, and the need for counselling, accounting for the positive responses accounting for the positive responses with the average rate of 78.8%; 87.5% and 82.5%, correspondingly. There was a significant difference in the Clinic's need for pharmaceutical care services among patients of different age groups (p = 0.043).Discussion: A significant difference was observed in the need for pharmaceutical care services among patients of different age groups, highlighting the importance of tailored approaches to meet the diverse needs of the patient population effectively. At the same time, the patient's satisfaction and demand for pharmaceutical care services account for a large proportion.
Keywords: Family medicine; Pharmaceutical care; Primary health care.